Energy Security: An Interdisciplinary Approach - Bahgat, Gawdat (Wiley, 2011)
Security of Energy supply is a major concern for all modern societies, intensified by skyrocketing demand in India and China and increasing international competition over fossil fuel deposits. Energy Security: An Interdisciplinary Approachgives A comparative analysis from both consumers' and producers' perspectives. It uniquely combines economics, geology, international relations, business, history, public management and political science, in one comprehensive volume, highlighting the vulnerabilities and need to move to more sustainable energy sources.The author provides a number of useful case studies to demonstrate the theory, including perspectives from consuming regions such as the United States, the European Union, and China, and from exporting regions; the Middle East, Africa, Russia and the Caspian Sea.Key features include:coverage on theoretical and empirical frameworks so readers are able to analyse concepts relevant to new laws and policies in energy securityup-to-date coverage on ‘green energy', outlining research on the balance between meeting energy needs and avoiding polluting the environmentan examination of the three most prominent international energy organizations; International Energy Agency, International Energy Forum, and Organization of Petroleum Exporting Countriesa full Glossary listing all important terms used in the energy fieldThis study holds important information for policymakers, politicians, energy specialists, scientists and post-graduate and final year students of energy and international relations. With its clear written style, it will also engage other professionals who are interested in international political economy and the future of global energy.